Cooperative supramolecular polymerization of styrylpyrenes for color-dependent circularly polarized luminescence and photocycloaddition - Yuan, Wei (2024)
Developing facile and efficient methods to obtain circularly polarized luminescence (CPL) materials with a large luminescence dissymmetry factor (glum) and fluorescence quantum yield (ΦY) is attractive but still challenging. Herein, supramolecular polymerization of styrylpyrenes (R/S-PEB) is utilized to attain this aim, which can self-assemble into helical nanoribbons. Benefiting from the dominant CH-π interactions between the chromophores, the supramolecular solution of S-PEB shows remarkable blue-color CPL property (glum: 0.011, ΦY: 69%). From supramolecular solution to gel, the emission color (blue to yellow-green) and handedness of CPL (glum: -0.011 to +0.005) are concurrently manipulated, while the corresponding supramolecular chirality maintains unchanged, representing the rare example of color-dependent CPL materials. Thanks to the supramolecular confine effect, the [2 + 2] cycloaddition reaction rate of the supramolecular solution is 10.5 times higher than that of the monomeric solution. In contrast, no cycloaddition reaction occurs for the gel and assembled solid samples. Our findings provide a vision for fabricating multi-modal and high-performance CPL-active materials, paving the way for the development of advanced photo-responsive chiral systems.